On a Model for Prediction of the Movements of a Crowd in Narrow Exits - Kotulski, Z.; Szczepiński, W. (Engineering Transactions, 2005)
In the paper a method of simulation of the movement of a crowd in narrow exits is presented. The stochastic model applied is based on the concepts proposed by J. Litwiniszyn concerning the analysis of movements of earth masses caused by underground mining works. The main part of the paper contains the results of mechanical simulation of the crowd movement in several geometrical configurations of the exits. The concluding sections of the paper present the diffusion interpretation of the obtained experimental results and a proposition of further research based on several practical models of movement of granular material.